Response to: Relation of circumferential and longitudinal strain to other independent prognostic imaging markers in first time ST-elevation myocardial infarction - Buß, Sebastian Johannes; Giusca, Sorin; Korosoglou, Grigorios (International journal of cardiology, 2016)
We highly appreciate the letter from Garg and colleagues in regard to our recent article. - However, some points need to be mentioned, which may further help with the interpretation - of our study. Firstly, we are absolutely aware of the limitations and pitfalls, when - using this method, especially for regional radial strain the reproducibility is worse - than for circumferential strain parameters. Therefore it was not the intention of - our article to suggest that the strain assessment by feature tracking imaging (FTI) - is the sole technique for the evaluation of post-infarct remodeling or the new standard - technique for myocardial deformation imaging.
Published:July 31, 2015
Gesehen am 28.04.2020